Abstract 066: Mechanical Thrombectomy Access in Africa: A Mission Thrombectomy (MT‐2020 Plus) MT‐GLASS Study Sub‐Analysis - Gabriela Alejo; Kaiz Asif; Oliver Otite; Mehari Gebreyohanns; Shashvat Desai; Erica Jones; Dileep Yavagal; Santiago Ortega‐Gutierrez (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Despite the well‐established potent benefit of mechanical thrombectomy (MT) for large vessel occlusion (LVO) stroke, access to MT remains low globally, particularly in Africa. We compared the access to MT in Africa versus access in other regions of the globe. Methods Mission Thrombectomy conducted a survey in 75 countries between November 22, 2020, and February 28, 202 to assess the access to mechanical thrombectomy and its determinants. Mechanical thrombectomy access (MTA) was defined as the estimated proportion of patients with LVO receiving MT annually. The current MT operator availability was defined as ([current MT operators x 50/current annual number of estimated thrombectomy‐eligible LVOs] x 100) and the current MT center availability was defined as ([current MT centers x 150/current annual number of estimated thrombectomy‐eligible LVOs] x 100). Baseline survey responses in Africa versus the rest of the world were summarized using descriptive statistics. Between group differences in baseline characteristics were evaluated using the Wilcoxon rank‐sum test Results Of all 61 countries included in the final analysis, 14.8% (n=9) were from the African continent. Median MT access in Africa (0.4%) was about 10% of that of the rest of the world (4.9%). Country‐level summary characteristics of different determinants of MT access in Africa vs the rest of the world are presented in Table 1. Less than 50% of African countries (44.4%) have prehospital medical services, compared to 84.6% in the rest of the world (p‐value for comparison =0.007). In generalized linear models, LVO stroke patients in Africa had 90% lower odds of MT access when compared to the rest of the world (OR 0.10, 95%CI 0.04‐0.22). Conclusion Access to MT in Africa is extremely low and far below that of other regions of the globe. Public health interventions must be prioritized to increase access to MT in the continent of Africa.